Confirmation of Elaphria agrotina (Guenée, 1852) (Lepidoptera: Noctuidae) feeding on sugarcane - Nascimento, Vinícius F.; Lacerda, Letícia B. de; Peixoto, Pedro G.; Ramalho, Dagmara G.; Souza, Joice M. de; Silva, Sarah C. da; Matos, Gilson F. de; De Bortoli, Sergio A. (Entomological Communications, 2024)
This study reports the observation of Elaphria agrotina (Guenée, 1852) (Lepidoptera, Noctuidae) attacking sugarcane (Saccharum spp.). These specimens were collected in a sugarcane field under renovation while feeding on bait traps made from sugarcane stalks. Larvae were also detected within soil layers up to 6 cm deep, near to crop residues and rhizomes. Notably, they were found on sugarcane plants displaying 'dead heart' symptoms. The presence of this species in bait of sugarcane stalks raises concerns about potential secondary damage to the crop, which is already susceptible to other pests, and the possibility of it causing infestations in healthy plants.